The Effect of P2P Lending on Economic Growth in Indonesia with MSMEs as a Mediating Variable - Ade Lia Septiana Putri; Alfindo Wira Yudha Pradana; Fany Noor Fadilla; Ilham Agista Putranto; Sharah Agastya; Zaki Prafitra Haya (Fakultas Syariah IAIN Langsa, 2026)
The development of digital financial technology is expected to expand access to productive financing and promote inclusive economic growth through the strengthening of micro, small, and medium enterprises (MSMEs). However, despite the rapid growth of peer-to-peer (P2P) lending in Indonesia, which reached IDR 763.14 trillion in 2023, empirical evidence on the transmission mechanism of its impact on economic growth—particularly through the role of MSMEs—remains limited. This study aims to analyze the effect of P2P lending on Indonesia’s economic growth during the 2019–2023 period, with the number of MSMEs serving as a mediating variable. Employing a quantitative approach, this study utilizes provincial-level panel data covering gross regional domestic product (GRDP), total P2P lending disbursement, and the number of MSMEs, and estimates the model using panel regression and mediation analysis. The results indicate that P2P lending has a positive and significant effect on economic growth, both directly and indirectly through MSMEs, with the mediating role being partial. Academically, this study contributes to the digital finance literature by highlighting the role of MSMEs as a transmission channel for economic growth, while from a policy perspective, the findings provide empirical support for strategies aimed at strengthening fintech lending and sustainably empowering MSMEs.